CREATION OF TOOLS FOR THE DEVELOPMENT OF THE ENTERPRISE - SUBJECT OF ZED - Andriy Didyk; Yurii Pogorelov; Vasyl Lemishovskyi; Anton Lazarev (Фінансово-кредитна діяльність: проблеми теорії та практики)
The purpose of the article is to consider tools for the development of enterprises that are subjects of foreign economic activity (FEA). The consequences of the war against Ukraine create a compelling need for the development of the national Ukrainian economy. Analyzing the foreign experience of different countries in the post-war period indicates that export activities are one of the most reasonable vectors for such development, both at the level of individual enterprises and at the level of the national economy as a whole. Strengths, weaknesses, opportunities, and threats have been identified for Ukrainian enterprises operating in the field of foreign economic activity. It is shown that the number of threats has increased compared to the pre-war period. Despite the significant number of threats and weaknesses, the analysis shows that Ukrainian enterprises have a "window of opportunities" that can be effectively used. Using dichotomous criteria for the possibility of entering foreign markets and the potential of the domestic market, a matrix of strategic choice has been developed. This matrix is intended for use at the level of individual enterprises. A reasonable strategic choice for the enterprise is determined for each quadrant of this matrix in the general version, and industry-specific recommendations are considered. Based on formulated key questions, necessary development tasks are identified for enterprises as subjects of foreign economic activity. These tasks include strategic goal setting, determination of the competitive advantage used, and development of the enterprise strategy. Necessary management tools are proposed and described for the implementation of each of these tasks. A set of key questions has been developed for the chosen model of enterprise development strategy to determine the content of the elements of such a strategy. The usage of proposed development tools for subjects of foreign economic activity is briefly presented using the example of automotive industry enterprises.